Women in Lebanon : living with Christianity, Islam, and multiculturalism - Thomas, Marie-Claude (Palgrave Macmillan, 2020)
Combining insider and outsider perspectives, Women in Lebanon looks at Christian and Muslim women living together in a multicultural society and facing modernity. While the Arab Spring has begun to draw attention to issues of change, modernity, and women's subjectivity, this manuscript takes a unique approach to examining and describing the Lebanese "alternative modernities" thesis and how it has shaped thinking about the meaning of terms like evolution, progress, development, history, and politics in contemporary Arab thought. The author draws on extensive ethnographic research, as well as her own personal experience.